Kasih Sayang Manusia terhadap Hewan Peliharaan Studi Hadis Tematik - Oktaviona Oktaviona; Masrukhin Muhsin; Salim Rosyadi (STIKes Ibnu Sina Ajibarang, 2025)
Overall, human affection for pets creates a mutually beneficial relationship. Pets get the attention and care they need, while humans gain valuable emotional, physical, and social benefits from interacting with their pets. In Islam, there are hadiths and understandings that discuss human affection for pets. This study uses a qualitative method, data collection techniques using methods that can produce descriptive data, namely data written in a book, books, journals, articles and scientific works. The understanding of scholars about the hadiths of human affection for pets affection for pets which includes: the reward of loving animals has a friendly nature, namely affection, empathy, and gentleness towards fellow creatures, doing good and showing affection to all living things. Helping animals can erase sins helping animals can be a means to get forgiveness from Allah for sins that have been committed. An example is the hadith about a prostitute whose sins were forgiven because she gave a thirsty dog ​​a drink.